Geographic Analysis of Distribution and Development of Goat Farms - Qamara, Cori; Yuzaria, Dwi; Madarisa, Fuad (Jurnal Agripet, 2024)
This study investigates the distribution and development of goat farms in Limapuluh Kota District with two main objectives: (a) to map the spatial distribution and development areas of goat farms, and (b) to enhance the capacity of the goat population within the district. Spatial analysis was conducted using ArcGIS 10.9, Location Quotient, and Shift Share Analysis to identify key areas for goat farm distribution and development. The capacity of livestock populations was evaluated through the CIRP method using Microsoft Excel, based on potential land resources. Secondary data from 2017 to 2021 on goat farm production was sourced from the Livestock and Animal Health Service Office and BPS Limapuluh Kota. Results indicated that goat farms are primarily concentrated in the Harau, Suliki, and Bukit Barisan Districts, while the Mungka, Payakumbuh, Guguak, Lareh Sago Halaban, and Kapur Sembilan Districts are identified as development areas. The Situjuh Limo Nagari, Luak, Akabiluru, and Pangkalan Koto Baru Districts are classified as consolidation areas, and the Gunuang Omeh District serves as a supporting area. The analysis highlights that 13 districts have potential for boosting the goat population, whereas Situjuh Limo Nagari and Guguak are categorized in the low group due to their goat population being below the threshold of 200 LU.